2020
DOI: 10.1002/jgm.3246
|View full text |Cite
|
Sign up to set email alerts
|

miR‐877‐5p alleviates chondrocyte dysfunction in osteoarthritis models via repressing FOXM1

Abstract: Background: The present study aimed to investigate whether forkhead box M1 (FOXM1), as a putative target of miR-877-5p, participated in interleukin (IL)-1βinduced cartilage degeneration in experimental osteoarthritis (OA) models in vitro and in vivo. Methods: In vitro and in vivo models of OA were established using IL-1β treated primary mouse chondrocytes and anterior cruciate ligament transection (ACLT) operation in mice. miR-877-5p mimics or agomir-miR-877-5p were used as therapeutic agents in both in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Recently, it is observed that FOXM1 expression has a potential prognostic value for prostate cancer, however, there is some evidence verifying that miR-877-5p can improve chondrocyte function of experimental osteoarthritis(OA) by targeting FOXM1 as a postulated molecular mechanism [ 18 , 39 ]. Then, the relationship between miR-877-5p and FOXM1 caught our attention, we speculated miR-877-5p may bind to FOXM1 to achieve the results of regulating cell biological function in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it is observed that FOXM1 expression has a potential prognostic value for prostate cancer, however, there is some evidence verifying that miR-877-5p can improve chondrocyte function of experimental osteoarthritis(OA) by targeting FOXM1 as a postulated molecular mechanism [ 18 , 39 ]. Then, the relationship between miR-877-5p and FOXM1 caught our attention, we speculated miR-877-5p may bind to FOXM1 to achieve the results of regulating cell biological function in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between miR-877-5p and FOXM1 were conducted in several studies. For example, miR-877-5p can affect cellular activities by regulating the transcription of forkhead box M1 (FOXM1) in osteoarthritis models [ 18 ]. Further, studies have also pointed out miR-877-5p suppresses cell proliferation through FOXM1 in gastric cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…miR-25 [ 15 ], miR-33-5p [ 16 ], miR-221, and miR-15b [ 17 ] have been revealed to act on corresponding targets, thus affecting the balance between bone formation and resorption, and therein regulating osteoblast differentiation. miR-877-5p is frequently downregulated in various cancers [ 18 20 ], and particularly, miR-877-5p has an alleviating impact on osteoarthritis chondrocytes [ 21 ]. In addition, miR-877-3p promotes osteoblast differentiation of MC3T3-E1 cells by targeting Smad7 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%